2008
DOI: 10.1073/pnas.0805909105
|View full text |Cite
|
Sign up to set email alerts
|

Energy-dependent fitness: A quantitative model for the evolution of yeast transcription factor binding sites

Abstract: We present a genomewide cross-species analysis of regulation for broad-acting transcription factors in yeast. Our model for binding site evolution is founded on biophysics: the binding energy between transcription factor and site is a quantitative phenotype of regulatory function, and selection is given by a fitness landscape that depends on this phenotype. The model quantifies conservation, as well as loss and gain, of functional binding sites in a coherent way. Its predictions are supported by direct cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
138
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(147 citation statements)
references
References 48 publications
9
138
0
Order By: Relevance
“…In the preceding analyses, it was assumed that selection favors maximum binding strength. Such a fitness function is justified by analyses of TFBSs in E. coli and S. cerevisiae that consistently infer a monotonic increase of fitness with increasing binding strength (15,30,31). Nonetheless, situations likely exist in which an intermediate phenotype is favored.…”
Section: Significancementioning
confidence: 99%
“…In the preceding analyses, it was assumed that selection favors maximum binding strength. Such a fitness function is justified by analyses of TFBSs in E. coli and S. cerevisiae that consistently infer a monotonic increase of fitness with increasing binding strength (15,30,31). Nonetheless, situations likely exist in which an intermediate phenotype is favored.…”
Section: Significancementioning
confidence: 99%
“…We obtain a simple quantitative model of compensatory evolution by applying a bioenergetic, information-based model of transcriptional regulation (Von Hippel and Berg 1986;Gerland et al 2002;Mustonen et al 2008;Tulchinsky et al 2014). We give an overview here and refer the reader to Tulchinsky et al (2014) for details.…”
Section: Modelmentioning
confidence: 99%
“…Our shorthand follows a distinction made by evolutionary geneticists when offering alternative explanations, pleiotropy vs. linkage disequilibrium, for correlations between evolving traits (e.g., Hartl and Clark 2007). We characterize the one-domain TF as being mechanistically pleiotropic, while the two-domain TF serves as a control for the potential effects of maximal linkage disequilibrium between otherwise mechanistically independent regulatory sites.We obtain a simple quantitative model of compensatory evolution by applying a bioenergetic, information-based model of transcriptional regulation (Von Hippel and Berg 1986;Gerland et al 2002;Mustonen et al 2008;Tulchinsky et al 2014). We give an overview here and refer the reader to Tulchinsky et al (2014) occupancy-the probability that a TF is associated with its cis-regulatory site at any given moment.…”
mentioning
confidence: 99%
“…This model assumes the positions within the binding site are independent, and the contribution at one position of the binding site to the overall affinity does not depend on the identity of nucleotides in other positions of the site. Despite the restrictions imposed by this strong independence assumption, the PWM model has been successfully used to identify TF binding sites (TFBS) in sets of coexpressed genes (Stormo and Hartzell 1989;Roth et al 1998;Tavazoie et al 1999;Bussemaker et al 2001) as well as model TF binding site evolution (Doniger and Fay 2007;Mustonen et al 2008;Bradley et al 2010). Quantitative analysis of high-throughput binding data has also shown that PWMs are a good quantitative model for most TFs (Zhao et al 2009;Zhao and Stormo 2011).…”
mentioning
confidence: 99%